2011
DOI: 10.1186/1752-1947-5-212
|View full text |Cite
|
Sign up to set email alerts
|

Traditional electrosurgery and a low thermal injury dissection device yield different outcomes following bilateral skin-sparing mastectomy: a case report

Abstract: IntroductionAlthough a skin- and nipple-sparing mastectomy technique offers distinct cosmetic and reconstructive advantages over traditional methods, partial skin flap and nipple necrosis remain a significant source of post-operative morbidity. Prior work has suggested that collateral thermal damage resulting from electrocautery use during skin flap development is a potential source of this complication. This report describes the case of a smoker with recurrent ductal carcinoma in situ (DCIS) who experienced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In a retrospective study of 151 SSMs there was no significant difference between diathermy and scalpel. Despite this, dissection devices with a low risk of low thermal injury are being proposed in an attempt to minimize skin flap necrosis.…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective study of 151 SSMs there was no significant difference between diathermy and scalpel. Despite this, dissection devices with a low risk of low thermal injury are being proposed in an attempt to minimize skin flap necrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have published information on the applications of electrosurgical instruments during clinical surgery. Thermal damage and the sticking problem are critical challenges that affect the use of minimally invasive electrosurgical devices . The thermal damage induced by minimally invasive electrosurgical instruments can damage surrounding important organs and tissues .…”
Section: Introductionmentioning
confidence: 99%
“…Thermal damage and the sticking problem are critical challenges that affect the use of minimally invasive electrosurgical devices. 3,4 The thermal damage induced by minimally invasive electrosurgical instruments can damage surrounding important organs and tissues. 5 A sticking problem generates physical injury by a pulling force on the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, electrosurgery has been performed to treat tumors from the orofacial excision. However, electrosurgical units are also known to pose serious threats such as tissue adherence and thermal damage of the surrounding tissue . The treatment position of orbital surgery is very close to eyes during clinical electrosurgery as shown in Figure , so it needs to prevent excessive thermal damage.…”
Section: Introductionmentioning
confidence: 99%
“…However, electrosurgical units are also known to pose serious threats such as tissue adherence 1 and thermal damage of the surrounding tissue. 2,3 The treatment position of orbital surgery is very close to eyes during clinical electrosurgery as shown in Figure 1, so it needs to prevent excessive thermal damage. Studies have shown that electrosurgical procedures may damage adjacent arteries, intestine, nerves, and bile ducts.…”
Section: Introductionmentioning
confidence: 99%